2020
DOI: 10.2340/00015555-3353
|View full text |Cite
|
Sign up to set email alerts
|

Ixekizumab Results in Persistent Clinical Improvement in Moderate-to-Severe Genital Psoriasis During a 52 Week, Randomized, Placebo-Controlled, Phase 3 Clinical Trial

Abstract: Genital skin is commonly affected among patients with psoriasis. Genital psoriasis can cause problems such as genital itch and pain, and have negative effects on mental, social, and sexual health. Ixekizumab, can provide significant relief of genital psoriasis within 12 weeks of starting treatment. This study showed that patients with genital psoriasis continue to have symptom relief after one year of treatment with ixekizumab. Ixekizumab was efficacious in treating moderate-tosevere genital psoriasis over 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 21 publications
(47 reference statements)
2
29
0
1
Order By: Relevance
“…After 12 weeks of brodalumab, sPGA‐G 0/1 was achieved by 16 of 18 patients (88.9%) and remained stable up to week 24 demonstrating its effectiveness. To our knowledge, no previous study has investigated sPGA‐G for brodalumab, although other anti‐IL17 molecules (i.e., ixekizumab) have demonstrated efficacy in genital psoriasis 36‐39 …”
Section: Discussionmentioning
confidence: 99%
“…After 12 weeks of brodalumab, sPGA‐G 0/1 was achieved by 16 of 18 patients (88.9%) and remained stable up to week 24 demonstrating its effectiveness. To our knowledge, no previous study has investigated sPGA‐G for brodalumab, although other anti‐IL17 molecules (i.e., ixekizumab) have demonstrated efficacy in genital psoriasis 36‐39 …”
Section: Discussionmentioning
confidence: 99%
“…Dosing could be increased if necessary to achieve or maintain satisfactory disease control. 6 Patients treated with IXE achieved persistent improvements in HRQoL, as measured by DLQI (0,1) and multiple domains of SF-36, and in the sexual impact of GenPs, at Week 12; these improvements persisted through Week 52. In the group that received IXE in both periods (IXE/IXE), the proportion of patients with GPSIS-Avoidance (1,2) response persisted through Week 52, with 80% (n = 24/30) achieving GPSIS-Avoidance (1,2).…”
mentioning
confidence: 88%
“…4,5 Ixekizumab (IXE), a high-affinity monoclonal antibody selectively targeting interleukin-17A (IL-17A), is the only United States Food and Drug Administration-approved treatment for patients with moderate-to-severe plaque psoriasis that includes labelling information about successful treatment of patients with genital involvement. 6 In the IXORA-Q trial, IXE provided significant improvements in HRQoL and in the sexual impact of GenPs following 12 weeks of treatment. 7,8 Here, we report the persistence of these improvements through 52 weeks.Patient eligibility criteria have been previously published 6-8 ; 149 patients were enrolled in the induction period (Weeks 0-12); patients randomised to either placebo (PBO) or Ixekizumab (IXEQ2W); most had GPSIS-Impact scores of ≥3 (moderate-tovery high), nearly one-third of patients had GPSIS-Avoidance score of 5 (always avoid sexual activity due to GenPs).…”
mentioning
confidence: 99%
“…Several papers have demonstrated significant improvement in genital lesion appearance, itch, sexual health, and quality of life in resistant genital psoriasis treated with ixekizumab. [49][50][51][52] A randomized, placebo-controlled, phase III clinical trial demonstrated the longterm efficacy and safety of ixekizumab for up to 52 weeks [51]. Patients received either ixekizumab 80 mg (n = 75) or placebo (n = 74) every 2 weeks up to week 12, then entered an openlabel period where all patients received ixekizumab 80 mg every 4 weeks up to week 52.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%